Cytodifferentiation during the spermatogenesis of the hermaphrodite caridea Exhippolysmata oplophoroides - Nunes, Erika Takagi; Braga, Adriane Araujo; dos Santos, Daniela Carvalho [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Among the decapods, the caridean Exhippolysmata oplophoroides has been described as a simultaneous protandric hermaphrodite, seeing that it presents a male initial stage followed by a hermaphrodite one in which it can function as male and as female. This work had the aims of characterizing the microscopical morphology of the male portion of the ovotestes gonads from E. oplophoroides, at the different development stages, identifying each cell from the germ lines during spermatogenesis, as well as describing the ultramorphology of spermatozoans in the terminal region of the vasa deferentia. Shrimps were collected in Ubatuba, north coast of São Paulo, and their male gonads and the ampoule were removed, fixed and processed according to histological routine and for scanning electron microscopy. The testicular portion is divided in lobes, inside which cells at the same stage of the spermatogenic cycle are observed, with prevalence of spermatogonia and spermatocytes at stages I, II and V of gonad development, whereas spermatids and spermatozoans are found at stages III and IV, respectively. Ultramorphology of the terminal portion of the vasa deferentia exhibits mature aflagellated spike-shaped spermatozoans, encased in secretion and between membrane foldings that will constitute the spermatophores. Despite presenting reproductive characteristics common to other decapods. E. oplophoroides shows spermatozoans as well as spermatophore with typical morphology, which is important for its identification and taxonomy. Further, this species showed polysaccharide secretions where the spermatozoa are immerse as far as the testicular portion, which could have a roe in their transport and nutrition as well as spermatophore constitution and/or fixation; differently, other caridean species begin spermatophore formation during the passage of the gametes through the vasa deferentia. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Exhippolysmata oplophoroides; Histology; Ultramorphology; Ovotestis; Spermatogenesis; Spermatophore